2013
DOI: 10.5533/dst-2177-8264-201325302
|View full text |Cite
|
Sign up to set email alerts
|

Association of sanitary pads and clothing with vulvovaginitis

Abstract: Introduction: Vulvar occlusion and moisture buildup resulting from the use of sanitary pads, synthetic underwear and/or tight pants are considered risk factors for the development of vulvovaginitis (VV). However, this association is still poorly elucidated. Objective: To associate the use of sanitary pads and clothing with the presence of bacterial vaginitis (BV) and vaginal candidiasis (VC). Methods: Cross-sectional study aimed at analyzing the use of sanitary pads and clothing in 307 volunteers from 18 to 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
1
4
0
2
Order By: Relevance
“…The study found that the participants women who did not wear damp clothing are less likely for vaginitis than those who wear it (B= -1.186-; P. value=0.047; OR= 3.273; 95% C.I = 1.018-10.523). These results are consistent with the study findings done by (13) which found that the usage of synthetic underwear has been linked to an increased risk of vaginitis. Janković et al, (2010) (14) discovered that women who used cotton-lined underwear had a greater incidence of vaginitis than those who did not (p=0.0001).…”
Section: Discussionsupporting
confidence: 93%
“…The study found that the participants women who did not wear damp clothing are less likely for vaginitis than those who wear it (B= -1.186-; P. value=0.047; OR= 3.273; 95% C.I = 1.018-10.523). These results are consistent with the study findings done by (13) which found that the usage of synthetic underwear has been linked to an increased risk of vaginitis. Janković et al, (2010) (14) discovered that women who used cotton-lined underwear had a greater incidence of vaginitis than those who did not (p=0.0001).…”
Section: Discussionsupporting
confidence: 93%
“…Although depilation products are used to facilitate genital and aesthetic hygiene, the aggression caused by the blades or other products used to remove hair from the genitalia may cause skin dryness, traumatize, and irritate the area. 29 A Brazilian study by Bardin et al 39 showed that 94.1% of participants used to have hair removed from their genital area, and most used a razor blade to do so. De Maria et al 40 stated in her their study that 60% of the participants presented at least one health complication due to the removal of pubic hair, the most common being epidermal abrasion and ingrown hairs.…”
Section: Discussionmentioning
confidence: 99%
“…The scope of scientific production on access and practices of menstrual hygiene was analyzed and organized by observation of recurrence, that is, by similarity of content, emerging three categories: 1) Access to dignified conditions for MHM ( 26 , 28 - 30 , 38 ) ; 2) Need for access to information ( 14 , 28 - 33 , 36 - 37 , 39 ) ; and 3) Practices for MHM ( 27 , 31 , 34 - 35 ) . The summary of the results identified by the studies in this review is presented in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%